Label-based protection scheme of vTPM secret - Xingshu CHEN; Wei WANG; Xin JIN (Tongxin xuebao)
The virtual trusted platform module (vTPM) played an important role in virtualization of trusted computing.According to security problems of existed vTPM,a protection scheme based on vTPM label was proposed.Firstly,a vTPM label was created for each virtual machine.This label had four main components,signature information,encryption information,measurement information and status information.Then,the security-enhanced vTPM dynamic migration protocol based on vTPM label status information was designed,to ensure the security of vTPM during live migration based on status information of vTPM label.Experiments show that the proposed scheme can protect vTPM secrets effectively and the increased performance cost during live migration is only 19.36%.